PENGARUH PELATIHAN HOLLOW SPRINT TERHADAP KECEPATAN DAN KEKUATAN OTOT TUNGKAI - Wirayuni, Ni Wayan (Universitas Pendidikan Ganesha, 2013)
This research aimed to determine the effect of hollow sprint training of the speed and leg muscle strength. This research type is a real experiment research design with randomized control goup pre-test post-test design. The research population was man’s of seventh grade students in SMP Negeri 1 Tegallalang school year 2012/2013 with total 118 people. Sample’s was 30 students who selected by random sampling technique. Speed ​​is measured with a 50 meter sprint, while the leg muscle strength was measured with back and leg dynamometer, followed the data were analyzed by independent t-test using SPSS 16.0. The independent t-test results showed: (1) the speed variable value t = 0.503 with significant value of 0.000. (2) the value of the variable leg muscle strength t = 2.398 with significant value of 0.000. The significance value is smaller than the value of α (0.05), thus the research hypothesis